(untitled) (Research, Society and Development, 2023)
Introduction: At the beginning of the outbreak caused by SARS-CoV-2 in 2019, it was necessary to create diagnostic methods for this new strain of the coronavirus family. Diagnosis was often difficult, and the best method to detect the infection was debated: serological or molecular testing. Objective: To compare the sensitivity, specificity and usability of serological and molecular tests in the detection of SARS-CoV-2. Methodology: This research is a systematic review. Results: Eight scientific articles and two diagnostic test package inserts were selected for this systematic review. The serological test in relation to usability does not present logistical difficulties, its cost-effectiveness in general is more accessible and only low-complexity physical spaces are required for its application. With regard to the sensitivity of the serological test, the average of the identified results was 85.7% for IgM and 92.8% for IgG. The average of Specificity reached 100% for both. On the other hand, the molecular test, with regard to usability, presents high difficulty in its logistics, its cost-effectiveness is high, it requires highly complex physical space with equipment restricted to this location (laboratory) and a highly qualified technical professional. In general, the percentages identified for Sensitivity were 95% and 100% for Specificity in detecting the SARS-CoV-2 virus. Conclusion: The molecular test proved to be more effective when compared to the serological test in detecting SARS-CoV-2 infection. On the other hand, with regard to usability, the serological test presented fewer obstacles compared to the molecular test.